Temporary Sternoclavicular Plating for an Unusual Double Clavicle Fracture (Medial Nonunion, Lateral Acute) Complicated by an Intraoperative Pneumothorax - John G. Skedros; Alex N. Knight; Chad S. Mears; Tanner D. Langston (Case Reports in Orthopedics)
Double (segmental) clavicle fractures, involving both the medial and lateral aspects of the clavicle, are very uncommon. Even less common is an asynchronous double fracture with one of the fractures being a nonunion. We report the case of a 30-year-old healthy male patient who had an unusual double clavicle fracture (medial nonunion, lateral acute) that occurred in separate traumatic events during motocross (motorcycle) racing. His fractures were treated surgically in two stages. In the first stage a long reconstruction plate was used that spanned onto the sternum and two transcortical screws were placed into the manubrium to enhance purchase for the deficient bone of the medial clavicle. In accordance with the preoperative plan, the medial one-third of the plate and the medial four screws (of the total 13 used) were removed. Although our patient had an excellent final result, he did have an intraoperative pneumothorax that was treated uneventfully with a chest tube. Medial clavicle fractures are difficult to treat, especially if they are nonunions and surgical complication rates can be high. Our case is one of the few that has been described where temporary sternoclavicular plating was successful in achieving an excellent long-term outcome.